STRATEGIC PLANNING OF SYSTEM INFORMATION STAFF PONDOK PESANTREN WITH ZACHMAN FRAMEWORK APPROACH - Latjuba Sofyana STT; Sri Anardani (STMIK Royal, 2022)
Abstract: The ABC Islamic boarding school is one of the Islamic boarding schools in Madiun Regency, in addition to the Islamic boarding schools in the Islamic boarding school there are also SMP and SMA which are under the same foundation. The ABC Islamic boarding school also applies information technology as a companion to its operational activities. The large number of employees and teachers in Islamic boarding schools, junior high schools and senior high schools creates difficulties in the staffing division for management. The management method that is currently running in the personnel department is deemed insufficient, because the existing information technology to support their work has not yet functioned optimally to support the strategy. The zachman framework is chosen so that planning is carried out in strategic steps, easy to understand and can be a control for future information system development. The results of this research are in the form of a blueprint for the system design which is mapped in the form of a Zachman matrix from the perspective of the Planner and Owner. Keywords: Information Systems, Strategic Planning, Zachman's Framework Abstrak: Pondok pesantren ABC merupakan salah satu Pondok Pesantren yang ada di Kabupaten Madiun, selain pondok pesantren di lingkungan ponpes tersebut juga terdapat SMP dan SMA yang dinaungi satu yayasan yang sama. Pondok pesantren ABC juga menerapkan teknologi informasi sebagai salah satu pendamping kegiatan operasional nya. Banyaknya karyawan dan guru yang terdapat di pondok pesantren, SMP dan SMA menimbulkan kesulitan pada bagian kepegawaian untuk pengelolaannya. Cara pengelolaan yang sedang berjalan di bagian kepegawaian dirasa tidak lagi mencukupi, karena teknologi informasi yang ada untuk menunjang pekerjaan mereka belum berfungsi optimal sebagai pendukung strategi. Kerangka kerja zachman dipilih agar perencanaan dilakukan dengan langkah-langkah yang strategis, mudah dipahami dan bisa menjadi kontrol untuk pengembangan sistem informasi ke depan. Hasil penelitian ini berupa blue print rancangan sistem yang dipetakan didalam bentuk matrik Zachman yang dilihat dari sudut pandang Planner dan Owner. Kata kunci: Kerangka kerja Zachman, Perencanaan Strategis, Sistem Informasi